Who Owns Web Services Management? where does it belong?. - Foody, Dan (SOA webservices journal.)
When I tell customers that my company does Web services management, the question I often hear is "so what do you mean by Web services management?" It's no wonder there's so much confusion on this issue, because the term "management" has been used to mean many different things. For example, there's business process management (actively coordinating the runtime execution of business processes) and systems management (passively monitoring performance and availability of IT infrastructure). These are two very different meanings for the word "management" and two very different markets.